THE STUDENT IMPROVE IN LEARNING RESULTS ON CIVIC EDUCATION USING PROBLEM BASED LEARNING MODEL IN CLASS V IN ELEMENTARY SCHOOL - Rosfarina, Amalia; Alwi, Elma; Amerta, Sri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
AbstractThis research aims was to describe the improvement of the student`s on learning Civics using PBL model. Using qualitative and quantitative approach . Type of research that is research action class . This Subject of this research an teachers and students. Students as many as 20 people .The research procedure includes (1) planning, (2) implementation, (3) observation, and (4) reflection. The result of the research indicated that the student`s learning achievement improved first cycle  from average of 72,66 with qualification fication Good (B) and second cycle  average 89,68 with excellent qualification (SB) Hence, the use of Problem Based Leammg (PBL) model can improve student learning outcomes in elementary school (SD)Keyword :The result of study, Civic Education, and Problem Based Learning (PBL)